Diversity of epiphytic bryophytes of the Colombian Amazon (2016)
Abstract. This thesis deals with the bryoflora, structure, and diversity of the communities of epiphytic bryophytes in a vertical gradient in four lowland rain forests of the Colombian Amazon. The gradient was studied in four sites and included 64 phorophytes across 2300 km2. Each phorophyte was divided into six height zones. In order to carry out the sampling from the base to the top of the trees, we climbed the trees, using the static rope technique. In this thesis I present a taxonomic and floristic study. Eighteen new records of epiphytic bryophytes to Colombia and 109 new departamental records are reported. Each new record for Colombia is provided with comments, illustrations, and a description of diagnostic characteristics for each taxon. Information about localities, altitude, and distribution on the trees is also given. Many of these new records were from the forest canopy. The high number of new records was to be expected since the canopy of the Amazonian forests of Colombia has been little studied. The study presents the first inventory of epiphytic bryophytes across the Colombian Amazon, with 2827 records of bryophytes recorded from 64 trees sampled from the base to the canopy. Our inventory contained 160 species (116 liverworts and 44 mosses), distributed in 26 families and 64 genera. The average number of species per locality was 75, and the average number per plot was 9. We found floristic similarities among localities in the Colombian Amazon. Species richness was similar among the sites, except for Putumayo, where the number of species was slightly higher, very possibly influenced by species migrating from the northern Andes. We also determined that the species were distributed in a clear vertical zonation pattern along the host trees, suggesting that the species composition of the epiphytic bryophyte communities at local and regional scales can be explained by niche assembly. This conclusion is also supported by the presence of a high percentage of indicator species across the Colombian Amazon, showing a high specificity of species for a particular microhabitat within the forest. Finally, we provide a genetic population study conducted with molecular techniques, using the liverwort Cheilolejeunea rigidula as our model species, which shows that growth can be found from the base of the trunk to the upper canopy. For this study we included individuals from Guayana and Brazil to determine the connectivity and genetic structure of this species across the Amazon region. The statistical analyses and molecular data allowed us to establish the presence of a clear genetic differentiation. The spatial structure of the ITS indicated an east-to-west and north-to-south gradient with a gradual differentiation of subpopulations. The gradient is additionally supported by a weak relationship between genetic distance and geographic distance. The further apart the individuals are, the less similar their genetic structure is, indicating limitations not in the dispersion but in the sexual reproduction of Cheilolejeunea rigidula. The genetic structure of the subpopulations of C. rigidula provided us with insights into the evolution of tropical liverworts.